2011
DOI: 10.1007/s12562-011-0421-0
|View full text |Cite
|
Sign up to set email alerts
|

Influence of offshore breakwaters on fish assemblage structure in the surf zone of a sandy beach in Tokyo Bay, central Japan

Abstract: To determine the effects of shore-parallel offshore breakwaters on the surf-zone fish assemblage structure of a sandy beach, three study sites (sheltered inshore of breakwater, between adjacent breakwaters, and exposed without breakwaters) were sampled at Ohnuki . Although some physical variables (wave height, turbidity, and water depth) differed among the three sites, no differences were apparent among the sites in the numbers of fish species and individuals, or in the abundance of epibenthic invertebrates (a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 32 publications
0
5
0
Order By: Relevance
“…These two contrasted conditions may occur at both sides according to wind conditions (Lima & Vieira 2009; Mont'Alverne et al , 2012) resulting in no overall differences in fish assemblage structure in both sides of the jetties. In fact, some recent studies have suggested that surf zone fish assemblage is not particularly affected by the presence of jetties or breakwaters (Cenci et al , 2011; Mikami et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…These two contrasted conditions may occur at both sides according to wind conditions (Lima & Vieira 2009; Mont'Alverne et al , 2012) resulting in no overall differences in fish assemblage structure in both sides of the jetties. In fact, some recent studies have suggested that surf zone fish assemblage is not particularly affected by the presence of jetties or breakwaters (Cenci et al , 2011; Mikami et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Many other families (n = 43), including turbot (Scopthalmidae), are scarce in most surf zones, but can be common in some locations (Vinagre, Silva, Lara, & Cabral, 2011) ( Figure 4). By contrast, few families (n = 10), for example mullet and herring (Clupeidae), are common and numerically dominate surf fish assemblages (Mikami, Nakane, & Sano, 2012) (Figure 4).…”
Section: Diversity and Composition Of Fish Assemblages In Global Sumentioning
confidence: 99%
“…Beach nourishment studies either report no significant effects on fish assemblages (Ross & Lancaster, 2002) or describe impacts to fish abundance, diversity and diet (Manning, Peterson, & Fegley, 2013;Wilber, Clarke, Ray, & Burlas, 2003b). Studies on the effects of artificial structures either report no impact of jetties or breakwaters on fish assemblages (Mikami et al, 2012;Rodrigues & Vieira, 2012) or outline changes to fish abundance and diversity that are attributed to the construction of groins (Tatematsu et al, 2014).…”
Section: Humans and Surf Fishes: Habitat Modification Fishing And mentioning
confidence: 99%
“…The second dominant species of the ZRf group was P. microcephalus. They are widely distributed in tropical and subtropical areas in the coastal waters of Beibu Gulf, south of Hainan Island, China at 17-18 o N 53 and Ohnuki Beach, Tokyo Bay, Japan at 35 o N 54 . The group of P. microcephalus composed two cohorts in our November survey.…”
Section: Discussionmentioning
confidence: 99%